The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/2177-9465-ean-2018-0122
|View full text |Cite
|
Sign up to set email alerts
|

Continuous positive pressure on aircraft in neonates: care provided by the nursing team

Abstract: Objective: to describe the nursing care of the neonate in continuous positive airway pressure (CPAP) with prong analyzing them in the light of the systematization of nursing care / process. Method: Descriptive research, qualitative approach. We interviewed 30 nursing professionals from the neonatal intensive and intermediate care units of a school hospital in Maceió / Alagoas, from August / 2016 to January / 2017, through a semi-structured interview, in the light of Bardin's content analysis. Results: Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…While another study that aimed to test the application of hydrocolloid in a double layer, that is, in the nostrils and in the high-flow nasal catheterprong, observed that the cases that presented favorable results may have been due to the vigilant care of the teams of neonatal unit nursing, an extremely relevant factor for the protection and care of the skin of premature newborns (18)(19) . In that investigation, the hydrocolloid patch used in only seven babies was placed when the injury was already present, differing from the studies in which its use was recommended as protection against the appearance of septal injuries (7,9,(12)(13) . There is evidence in the literature of other forms of treatment for septal injuries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While another study that aimed to test the application of hydrocolloid in a double layer, that is, in the nostrils and in the high-flow nasal catheterprong, observed that the cases that presented favorable results may have been due to the vigilant care of the teams of neonatal unit nursing, an extremely relevant factor for the protection and care of the skin of premature newborns (18)(19) . In that investigation, the hydrocolloid patch used in only seven babies was placed when the injury was already present, differing from the studies in which its use was recommended as protection against the appearance of septal injuries (7,9,(12)(13) . There is evidence in the literature of other forms of treatment for septal injuries.…”
Section: Discussionmentioning
confidence: 99%
“…NIV has therapeutic advantages for the recovery of newborns with respiratory problems, however, the use of prongs without preventive care can result in injuries and may cause deformities, nasal asymmetry and airway obstruction (6,(8)(9) . Nasal trauma among premature babies due to the use of prongs can vary between 20 and 60% worldwide and in Brazil it can reach percentages from 70 to 100% (10,16) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations